2015
DOI: 10.19070/2332-290x-si03001
|View full text |Cite
|
Sign up to set email alerts
|

Venous Ocular Blood Flow in Primary Open Angle Glaucoma

Abstract: However few of them mention the role of venous blood flow in glaucoma and explore its link to disk hemorrhages, retinal vein occlusion [18] and retinal venous pulsation [14,15].The purpose of our study was to evaluate venous blood flow in Special Issue on "Understanding Glaucoma"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
1
4
0
1
Order By: Relevance
“…We have recently revealed that ocular blood flow was significantly reduced both in NTG and HTG compared to healthy subjects. The reduction of arterial ocular blood flow was more significant in HTG than in NTG while the lower venous blood flow was detected in NTG patients [ 18 ]. It was emphasized in literature that the reduction of blood flow velocities in the central retinal vein and central retinal artery was significantly associated with glaucoma progression both in NTG and HTG patients with well controlled IOP (21 mmHg or less) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently revealed that ocular blood flow was significantly reduced both in NTG and HTG compared to healthy subjects. The reduction of arterial ocular blood flow was more significant in HTG than in NTG while the lower venous blood flow was detected in NTG patients [ 18 ]. It was emphasized in literature that the reduction of blood flow velocities in the central retinal vein and central retinal artery was significantly associated with glaucoma progression both in NTG and HTG patients with well controlled IOP (21 mmHg or less) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A significant reduction of retrobulbar blood flow in NTG has been described in literature [ 17 , 18 ]. In addition, Kaiser et al demonstrated that ocular blood flow was reduced in both NTG patients and in those HTG patients which progressed despite a normal IOP [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, according to the CDI data, the parameters of retrobulbar blood flow in NTG were reduced significantly compared to healthy eyes that is in consistent with our previous data. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Pathological response to cold in patients with glaucoma has been previously demonstrated in our research [ 14 ] and we have described a significant reduction of retrobulbor blood flow in NTG. [ 15 ] Recently, some authors studied the peripheral blood flow in glaucoma patients after a cold provocation test (CPT) [ 1 ] and as a response to posture change. [ 16 ] Meanwhile, there is no literature data concerning the influence of CPT on HRV in NTG compared to healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Особенностью ПОУГ является бессимптомное течение и довольно сложная и трудоемкая диагностика на начальных стадиях, поэтому выявление данного заболевания в большинстве случаев происходит на стадиях, сопровождающихся уже необратимыми изменениями зрительного нерва [5]. ПОУГ -одна из главных причин слабовидения и слепоты среди лиц трудоспособного возраста в развитых странах [6].…”
unclassified